1989
DOI: 10.1136/jnnp.52.5.613
|View full text |Cite
|
Sign up to set email alerts
|

Auditory neglect.

Abstract: SUMMARY Auditory neglect was investigated in normal controls and in patients with a recent unilateral hemispheric lesion, by requiring them to detect the interruptions that occurred in one ear in a sound delivered through earphones either mono-aurally or binaurally. Control patients accurately detected interruptions. One left brain damaged (LBD) patient missed only once in the ipsilateral ear while seven of the 30 right brain damaged (RBD) patients missed more than one signal in the monoaural test and nine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(38 citation statements)
references
References 9 publications
1
33
1
3
Order By: Relevance
“…Furthermore, spatially tuned neuronal responses during sound localization (resembling those of primary auditory cortex) were demonstrated in the anterior ectosylvian fissure of the cat and the posterior parietal and prefrontal regions of primates 9-13 . Therefore, it was postulated that primary auditory cortex relies on these higher-order cortical regions for further processing of the spatial attributes of sound and its integration with other sensory modalities and motor function.Results of lesion studies in humans have been controversial; some studies attributed impaired sound localization exclusively to lesions in temporal lobe 14 , whereas others questioned its importance in sound localization 15 or reported auditory spatial deficits following parietal or frontal lobe lesions [16][17][18][19] . In a preliminary human PET study, we demonstrated activation in posterior parietal, lateral prefrontal and inferior temporal regions but not primary auditory cortex during sound localization 20 .…”
mentioning
confidence: 96%
“…Furthermore, spatially tuned neuronal responses during sound localization (resembling those of primary auditory cortex) were demonstrated in the anterior ectosylvian fissure of the cat and the posterior parietal and prefrontal regions of primates 9-13 . Therefore, it was postulated that primary auditory cortex relies on these higher-order cortical regions for further processing of the spatial attributes of sound and its integration with other sensory modalities and motor function.Results of lesion studies in humans have been controversial; some studies attributed impaired sound localization exclusively to lesions in temporal lobe 14 , whereas others questioned its importance in sound localization 15 or reported auditory spatial deficits following parietal or frontal lobe lesions [16][17][18][19] . In a preliminary human PET study, we demonstrated activation in posterior parietal, lateral prefrontal and inferior temporal regions but not primary auditory cortex during sound localization 20 .…”
mentioning
confidence: 96%
“…Пациенты не отвечают или не могут спонтанно определить местоположение стимула на левой стороне и кажется игнорируют эту часть пространства [58][59][60]. Необычный характер этого дефицита, высокая заболе-ваемость и его негативное влияние на восстановление стали причиной весьма продуктивной исследователь-ской работы в области когнитивной и клинической ней-робиологии и привели к разработке целого ряда методов реабилитации [11,[61][62][63][64].…”
Section: восходящий подход к реабилитации при игнорировании: пониманиunclassified
“…Patients fail to respond or to orient spontaneously to stimuli presented on the left side and seem unaware of this part of space. [58][59][60] The intriguing nature of the deficit, its high incidence, and its negative effect on recovery have initiated a highly productive research field in cognitive and clinical neuroscience, which has led to the development of several rehabilitation techniques. 11,[61][62][63][64] Several reviews and meta-analyses noted that although therapeutic interventions tended to alleviate neglect symptoms, this was not the case in all studies.…”
Section: Bottom-up Approaches To Neglect Rehabilitation: Understandinmentioning
confidence: 99%
“…Bisiach et al (1984) suggested that patients with USN showed more auditory localization errors compared to patients without USN, especially for sounds displayed in contralesional space. Many investigations have been carried out on auditory neglect and its manifestations (Bellmann et al 2001;De Renzi et al 1989;Pavani et al 2004). However, until now, no study has yet taken a specific interest in the mechanisms of spatial orienting of auditory attention in USN.…”
Section: Introductionmentioning
confidence: 99%